PEDAGOGICAL TESTING AS A MEANS OF EDUCATIONAL MONITORING: MANAGEMENT ASPECT - O.A. Charkina (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the problem concerning existing possibilities of pedagogical testing while forming monitoring system of education establishments on managers' level.